The bradycardic and hypotensive responses to serotonin are reduced by activation of GABA A receptors in the nucleus tractus solitarius of awake rats - Callera, J. C. [UNESP]; Colombari, Eduardo [UNESP]; De Luca Jr., L.A. [UNESP]; Menani, José Vanderlei [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2005)
We investigated the effects of bilateral injections of the GABA receptor agonists muscimol (GABA A) and baclofen (GABA B) into the nucleus tractus solitarius (NTS) on the bradycardia and hypotension induced by iv serotonin injections (5-HT, 2 µg/rat) in awake male Holtzman rats. 5-HT was injected in rats with stainless steel cannulas implanted bilaterally in the NTS, before and 5, 15, and 60 min after bilateral injections of muscimol or baclofen into the NTS. The responses to 5-HT were tested before and after the injection of atropine methyl bromide. Muscimol (50 pmol/50 nl, N = 8) into the NTS increased basal mean arterial pressure (MAP) from 115 ± 4 to 144 ± 6 mmHg, did not change basal heart rate (HR) and reduced the bradycardia (-40 ± 14 and -73 ± 26 bpm at 5 and 15 min, respectively, vs -180 ± 20 bpm for the control) and hypotension (-11 ± 4 and -14 ± 4 mmHg, vs -40 ± 9 mmHg for the control) elicited by 5-HT. Baclofen (12.5 pmol/50 nl, N = 7) into the NTS also increased basal MAP, but did not change basal HR, bradycardia or hypotension in response to 5-HT injections. Atropine methyl bromide (1 mg/kg body weight) injected iv reduced the bradycardic and hypotensive responses to 5-HT injections. The stimulation of GABA A receptors in the NTS of awake rats elicits a significant increase in basal MAP and decreases the cardiac Bezold-Jarisch reflex responses to iv 5-HT injections.
Keywords: Muscimol; GABA receptors; Nucleus tractus solitarius; Parasympathetic component; Bezold-Jarisch reflex; Awake rats